Exploring Digital Wallet Preferences and Challenges Among Accounting Students: Menjelajahi Preferensi dan Tantangan Dompet Digital di Kalangan Mahasiswa Akuntansi - Nisa’, Khoirun; Abidin, Fityan Izza Noor (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the preferences and obstacles faced by Muhammadiyah University of Sidoarjo (UMSIDA) accounting students in using digital wallets. Using a qualitative approach, data was collected through interviews, participant observation, and documentation. Results reveal that ShopeePay was the preferred choice due to its necessity for online shopping, followed by DANA for its affordability in mobile top-ups. Technical obstacles, such as transaction troubles and application errors, were encountered by some students. These findings highlight the importance of addressing technical issues and promoting awareness of digital payment security to facilitate smoother adoption of digital wallets among accounting students. Highlight: 1. Preferred Digital Wallets: ShopeePay and DANA chosen for necessity and affordability.2. Encountered Obstacles: Technical issues hinder smooth digital wallet usage.3. Importance of Solutions: Resolving tech issues crucial for wallet adoption. Keywords: digital wallets, accounting students, preferences, obstacles, qualitative research